Penerapan Metode Hill Al-Musykilah Pada Pembelajaran Maharah Al-Kalam Siswa Madrasah Aliyah - Masitoh, Harum; Nur Mufidah, Luk-Luk; Nurhayati, Anin (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2023)
Arabic is a subject that must be presented within the scope of madrasah learning. Arabic consists of 4maharah(skills), andmaharahwhich is considered the most important ismaharah al-kalam(speaking skills). Madrasa students are expected to be able to apply Arabic in the school environment. However, the majority of Aliyah madrasah students are embarrassed to express themselves using Arabic during learning. They tend to be rigid and are not used to expressing feelings and ideas in Arabic orally. To overcome this problem, teachers should choose and use the right method for learning Arabic, in particularmaharah al-kalam. The many and varied Arabic language methods must be adapted to the abilities and conditions of the students. In this article, the author will focus on discussing the application of the methodhill al-musykilat(problem solving) in learningmaharah al-kalam. This method is considered appropriate if applied to Aliyah madrasah students. With reasons, learning objectivesmaharah al-kalamcan be achieved with this method. As for one of the goals is that students are able to think and analyze problems, and express answers using Arabic orally in accordance with the problems that have been presented previously.